Quantitative contribution of the Grain for Green Program to vegetation greening and its spatiotemporal variation across the Chinese Loess Plateau. (22nd May 2022) - Song, Yi; Wang, Yunqiang; Jin, Long; Shi, Weiyu; Aryal, Jagannath; Comber, Alexis
Abstract: A distinct greening trend is evident in Asia, especially on the Loess Plateau (LP) of China, which is driven by climate change and large‐scale land‐use‐related ecological projects, especially the 'Grain for Green Program' (GFGP). However, the specific contributions of the GFGP to vegetation greening and the variation of this greening on a large spatiotemporal scale are not yet clear. We used long‐time‐series normalized difference vegetation index datasets and climate datasets based on the double mass curve method to quantify the contributions of ecological projects and climate change to the greening trend on the LP. We found that the interannual fluctuation of vegetation change was likely related to the interannual fluctuation of climate, especially precipitation. The increasing trend of vegetation change after 2005 indicated that the GFGP, as a type of external disturbance, began to improve vegetation growth. The GFGP failed initially to make a positive contribution in the first few years because of the drought conditions in 1999 and 2005. The increased precipitation played a critical role in enhancing the output of the GFGP on the LP after 2005. Then, the contribution of the GFGP increased quickly until 2013, after which it remained stable and reached average values of 58.8% ± 19.34% and 31.7% ± 24.3% in the representative areas that conducted the GFGP and in other regions with a lower implementation intensity of the GFGP, respectively. Our results highlight the contribution the GFGP has made to spatiotemporal variation due to the spatial heterogeneity of the projects, their intensity and the effect of forest stand age.